PUBLIC POLICY WITH AI: THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE POLICY PROCESS - Arief, Hanief; Radiwan, Radiwan; Karnadi, Karnadi; Choiruddin, Choiruddin; Muzakir, M Athar; Chairu, Trida (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
This research examines the role of artificial intelligence (AI) in public policy through a literature study approach. The background of the research is based on the rapid development of digitalization and the increasing need for innovation in governance. AI, as a data analysis and prediction tool, has the potential to improve the quality of decision-making and the efficiency of public administration. This study identifies various AI implementations in the health, transportation, and public service sectors in several countries, highlighting benefits such as improved service effectiveness and operational optimization. However, AI implementation also poses ethical challenges such as algorithmic bias, privacy issues, and lack of transparency in the decision-making process. The discussion in this study addresses policy recommendations to address these challenges as well as a comparison of AI adoption in developed and developing countries, providing insights into best practices and anticipated barriers. The research concludes that responsible AI adoption, supported by comprehensive regulation and capacity building of the apparatus, can significantly transform public policy.